Dietary grape seed proanthocyanidin extract regulates metabolic disturbance in rat liver exposed to lead associated with PPARα signaling pathway. (June 2018) - Yang, Daqian; Jiang, Huijie; Lu, Jingjing; Lv, Yueying; Baiyun, Ruiqi; Li, Siyu; Liu, Biying; Lv, Zhanjun; Zhang, Zhigang
Abstract: Lead, a pervasive environmental hazard worldwide, causes a wide range of physiological and biochemical destruction, including metabolic dysfunction. Grape seed proanthocyanidin extract (GSPE) is a natural production with potential metabolic regulation in liver. This study was performed to investigate the protective role of GSPE against lead-induced metabolic dysfunction in liver and elucidate the potential molecular mechanism of this event. Wistar rats received GSPE (200 mg/kg) daily with or without lead acetate (PbA, 0.5 g/L) exposure for 56 d. According to biochemical and histopathologic analysis, GSPE attenuated lead-induced metabolic dysfunction, oxidative stress, and liver dysfunction. Liver gene expression profiling was assessed by RNA sequencing and validated by qRT-PCR. Expression of some genes in peroxisome proliferator-activated receptor alpha (PPARα) signaling pathway was significantly suppressed in PbA group and revived in PbA + GSPE group, which was manifested by Gene Ontology analysis and Kyoto Encyclopedia of Genes and Genomes pathway analysis and validated by western blot analysis. This study supports that dietary GSPE ameliorates lead-induced fatty acids metabolic disturbance in rat liver associated with PPARα signaling pathway, and suggests that dietary GSPE may be a protector against lead-induced metabolic dysfunction and liver injury, providing a novel therapy to protect liver against lead exposure. Graphical abstract: Mechanism for GSPE ameliorating lead-induced liver metabolic disturbance. In rat liver, lead induced fatty acids metabolic dysfunction via oxidative stress-mediated inhibition of PPARα signaling pathway. However, GSPE maintained fatty acid metabolic homeostasis through abolishing lead-induced suppression of PPARα signaling pathway.Image 1 Highlights: Grape seed proanthocyanidin extract (GSPE) inhibits liver injury induced by lead exposure. Lead induces transcriptional dysregulation and ultimately contributes to metabolic unhomeostasis. GSPE activates PPARα signaling pathway to protect liver function against lead acetate exposure.